Synergistic effects of hyperbaric oxygen therapy combined with MPNFS nursing model on neurological recovery and recurrence prevention after chronic subdural hematoma surgery - Xie, Ying; Yang, Dongmei; Jiang, Ting; Liu, Hongdi; Gao, Yan (Frontiers in Neurology, 2025)
BackgroundChronic subdural hematoma (CSDH) has high postoperative recurrence rates. This study investigates the effects of hyperbaric oxygen therapy (HBOT) combined with Medical-Psychosocial-Nursing Functional Support (MPNFS) on functional recovery and recurrence prevention in CSDH patients, and establishes a recurrence prediction model.MethodsA total of 184 CSDH patients undergoing burr hole drainage were randomized into a control group and an observation group (HBOT + MPNFS). Neurological (NIHSS), motor (Fugl-Meyer Assessment), and quality-of-life (SF-36) outcomes were assessed preoperatively and at 1-month postoperatively. Complications and 6-month recurrence rates were recorded. Univariate/multivariate logistic regression identified recurrence risk factors, with ROC analysis evaluating predictive accuracy.ResultsThe observation group showed superior 1-month outcomes: lower NIHSS scores (t = 4.94, p < 0.001), higher FMA and SF-36 scores (p < 0.01). Complication and recurrence rates were significantly reduced (p < 0.05). Independent recurrence predictors included brain atrophy (OR = 2.877), poor brain reexpansion (OR = 3.165), preoperative hematoma width ≥ 20 mm (OR = 2.782), and absence of combined intervention (OR = 2.842). The multifactorial model achieved an AUC of 0.7862, indicating robust predictive efficacy.ConclusionHyperbaric oxygen therapy combined with MPNFS enhances neurological/motor recovery, improves quality of life, and reduces complications/recurrence in postoperative CSDH patients.